The mediating role of psychological capital on the relationship between authentic leadership and nurses' caring behavior: a cross-sectional study - Guowen Zhang; Wen Tian; Ying Zhang; Juanjuan Chen; Xiaohong Zhang; Wenfeng Lin; Huiping Li; Liqin Sun; Baozhen Cheng; Hui Ding; Guiqi Song (BMC, 2023)
Abstract Background Caring behavior among nurses would have an impact on patient outcomes. External organizational job resources and personal internal psychological resources are correlated to nurses' caring behavior. Authentic leadership and psychological capital were shown to be correlated with nurses' caring behavior in previous studies. However, the relationships among the three are nevertheless unclear. This study aimed to examine if psychological capital could act as a mediator between nursing managers' authentic leadership and nurses' caring behavior. Methods In December 2021, a total of 3,662 nurses were recruited from 37 hospitals in Anhui Province, China. They filled out online surveys, including general demographic information, the Authentic Leadership Questionnaire, the Psychological Capital Questionnaire, and the Caring Behavior Inventory. Structural Equation Modeling and the bootstrapping procedure were used to examine the mediating role of psychological capital. Results The scores of authentic leadership, psychological capital, and caring behavior of 3,495 nurses were 52.04 ± 13.24, 96.89 ± 17.78, and 104.28 ± 17.01, respectively. Psychological capital significantly mediated the relationship between authentic leadership and nurses' caring behavior (β = 0.378, p < 0.001, 95% confidence interval: 0.350 ~ 0.402), which made up 78.75% of the total impact (0.480). Conclusion The findings of this study suggested that nursing managers should develop an authentic leadership style, which can effectively improve nurses' caring behaviors toward patients in clinical practice. Meanwhile, nursing leaders should strengthen nurses' psychological evaluation and training, and promote nurses' caring behavior in clinical settings.